EFFECTS OF WATER SOLUBLE FRACTION OF CRUDE OIL AND DIETARY SUPPLEMENTATION OF ROSEMARY ON COMMON CARP (CYPRINUS CARPIO) - A. Y. Anwar; S. I. Mohammed; S. S. Omer (Journal of Animal and Plant Sciences, 2022)
This study was conducted to investigate the effects of water soluble fraction (WSF) of crude oil and dietary supplementation of rosemary on some physiological parameters of common carp (Cyprinus carpio). Common carp (mean weight = 30.41±2.28g) was exposed to (0, 3.57 and 7.14 ml/Lˡ) of WSF of crude oil and fed diets containing (0 and 0.1 %) of rosemary for 8 weeks. The experiment was arranged in completely randomized design (CRD) and data were analyzed through one-way ANOVA. The value of WG, SGR and survival were significantly (P≤0.05) decreased by exposure to WSF of crude and significantly (P≤0.05) enhanced by adding rosemary to exposed fish diet, while the FCR exhibited an opposite trend. The level of RBC, HGB, Hct, RBC, MCV, MCH, MCHC, WBC, LYM, GRA, MON, GOT and GPT were significantly (P≤0.05) decreased by exposing fish to WSF of crude oil, while the PLT, MPV cholesterol and LDL levels showed an opposite trends. Adding rosemary to exposed fish diet led a significant increase in the level of WBC, LYM, MON, MCH and MCHC. The results of this study showed that the WSF of crude oil have adversely affected the physiological parameters in common carp and dietary supplementation of rosemary could be one of the good approaches to reduce its negative effects.
Keywords: WSF of crude oil; Cyprinus carpio; growth performance; haematological parameters; biochemical parameters; rosemary